Problems of the introduction of passenger electric vehicles in the Krasnodar territory - Izyumsky, Alexander A.; Kotenkova, Irina N.; Nadiryan, Sofia L. (International journal of advanced studies, 2025)
Background.In this article, the authors consider the transition of passenger electric vehicles from internal combustion engines to cars that use electric motors partially or completely for movement, and also consider the problems that arise along this path using the example of the Krasnodar Territory as one of the regions most suitable for this transition. The article provides an analysis of the pace of development of the infrastructure necessary for the development of passenger electric transport in Russia and the Krasnodar Territory, assesses the current situation in the field of "electrification" of light vehicles, highlights the main problems that arise in this area, and outlines ways to solve them. The authors propose to carry out this transition not simultaneously and everywhere, timing it to certain dates, in accordance with certain fashion trends in the field of motor transport, but consistently and steadily, but taking into account the experience of other countries and their own specifics, in relation to each region of Russia. The authors provide recommendations for priority measures aimed at developing a passenger electric fleet and smoothing out problems with its implementation in relation to the Krasnodar Territory. Purpose. Identificationof the mainproblemsrelated to theintroductionof passengerelectricvehicles inthe KrasnodarTerritory. Materials and methods.The article used statistical analysis. Results.The analysis of the passenger electric fleet and the infrastructure necessary for its operation in the Krasnodar Territory was carried out, the problems arising on the way of introduction of passenger electric vehicles were studied and recommendations for an early and painless transition to electric vehicles were proposed. Scope of application of the results:scientific and research activities aimed at the early introduction of environmentally friendly vehicles.